Creating 3D printed sensor systems with conductive composites. (9th December 2020) - Lazarus, Nathan; Bedair, Sarah S
Abstract: Fused filament fabrication (FFF), the printing of parts through the deposition of layers of melted thermoplastic, is one of the most widely used 3D printing processes due to its ease of use, low cost and accessibility. In this work, integration of 3D printed sensors and interconnect between embedded components into a printed part is demonstrated in an FFF process for the first time. The use of printed active materials for sensing allows interactivity with the end user through mechanisms like touch and temperature. Through dual extrusion in a low cost commercial printer, printing of both a conductive thermoplastic composite and a non-conducting filament are combined to create complex patterns. The piezoresistive and thermally responsive properties of the thermoplastic composite are used to create several different sensor modalities including a piezoresistive strain sensor, a contact switch and a resistive temperature sensor. A heated insertion technique is then developed for embedding of electrical components. The conductive thermoplastic is also used to incorporate a 3D printed circuit board in the same part, including in-line embedding within the body of the part during the printing process. The sensor performance and component embedding properties are characterized, and the process is used to print systems including relaxation oscillators and op-amp interface circuits for sensor monitoring.